Flow-based sampling in the lattice Schwinger model at criticality - Albergo, Michael S.; Boyda, Denis; Cranmer, Kyle; Hackett, Daniel C.; Kanwar, Gurtej; Racanière, Sébastien; Rezende, Danilo J.; Romero-López, Fernando; Shanahan, Phiala E.; Urban, Julian M. (Physical review, 2022)
Recent results suggest that flow-based algorithms may provide efficient sampling of field distributions for lattice field theory applications, such as studies of quantum chromodynamics and the Schwinger model. In this work, we provide a numerical demonstration of robust flow-based sampling in the Schwinger model at the critical value of the fermion mass. In contrast, at the same parameters, conventional methods fail to sample all parts of configuration space, leading to severely underestimated uncertainties.
Online veröffentlicht am 29. Juli 2022
Gesehen am 10.01.2022